Czech Hosts Creating "a Real Home Away from Home" for North American Fertility Travellers - Speier, Amy (Anthropologica, 2015)
North American reproductive travel to the Czech Republic for in vitro fertilization (IVF) is kinship tourism—since it offers possibilities for creating a family. I turn attention to the intimate labour performed by IVF brokers, Czech doctors and hosts—who create a "home" for North Americans while they are in the Czech Republic. Also, North Americans who meet one another in the Czech Republic form bonds of social kinship. It becomes apparent how tourism processes profoundly shape kinship while at the same time relatedness shapes travel.